Beliefs About the World and Coping Strategies in Siblings of Adults with Intellectual Disabilities: The Moderating Effect of Posttraumatic Growth - Byra, Stanisława; Ćwirynkało, Katarzyna (Przegląd Badań Edukacyjnych (Educational Studies Review), 2024)
Research question: Is there a relationship between beliefs about the word and coping strategies in siblings of adults with intelectual disabilities (ID) and whether posttraumatic growth (PTG) moderates the association. Methods: One hundred and seventy-two siblings of people with ID were included in the sample. The main outcome measures used were the Post-Traumatic Growth Inventory (PTGI), the World Assumptions Scale (WAS) and the Coping Orientations to Problem Experienced (COPE).The studies were conducted in Poland. The associations between the variables were examined using correlation and moderation analyses. In the moderation model, beliefs about the world were posited as a predictor, PTG as the moderator, and coping strategies as outcome variables. Main results: Befiefs about the world were significantly associated with the different coping strategies. PTG (total score and indyvidual dimensions, except for spiritual changes) positively correlates with befiefs about the kindness of the world and has significant links with the various coping strategies. PTG moderates the association between befiefs about the world and coping strategies in siblings of adults with ID. Conclusions: Beliefs about the world and coping strategies are significantly related and their associations in moderated by PTG in siblings of adults with ID.